Performance evaluation of coated ceramics tool when turning hardened tool steel - 381446 Azizul Izzat Hashim (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2004